Prevalence of mutations in HBV DNA polymerase gene associated with nucleos(t)ide resistance in treatment-naive patients with Chronic Hepatitis B in Central China - Zhao,Youyun (2016)
Abstract Objective There are a lot of disagreements in the studies on hepatitis B virus (HBV) DNA polymerase mutation rate associated with nucleos(t)ide analogues (NAs) in treatment-naive chronic hepatitis B (CHB) patients. This is the first study aimed to investigate the prevalence of spontaneous HBV resistance mutations in Central China. Methods This study included treatment-naive patients with CHB from June 2012 to May 2015 receiving care at the Institute of Liver Disease in Central China. All patients completed a questionnaire covering different aspects, such as family medical history, course of liver disease, medication history, alcohol use, among others. Mutations in HBV DNA polymerase associated with NAs resistance were detected using INNO-LiPA assay. Results 269 patients were infected with HBV genotype B (81.4%), C (17.9%), and both B and C (0.7%). Mutations in HBV DNA polymerase were detected in 24 patients (8.9%) including rtM204I/V (n = 6), rtN236T (n = 5), rtM250V (n = 2), rtL180M (n = 2), rtT184G (n = 1), rtM207I (n = 1), rtS202I (n = 1), rtM204V/I & rtL180M (n = 5), and rtM204I & rtM250V (n = 1). Conclusion Spontaneous HBV resistance mutations in HBV DNA polymerase were found in treatment-naive patients with CHB in Central China. These findings suggest that we should analyze HBV DNA polymerase resistance mutation associated with NAs before giving antiviral therapy such as lamivudine (LAM), adefovir (ADV), and telbivudine (LdT).